2019
DOI: 10.1111/pace.13640
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the vein of Marshall involvement in mitral isthmus ablation

Abstract: Background Epicardiac conduction via the vein of Marshall (VOM) can bypass the mitral isthmus (MI) line, making MI ablation difficult. This study aimed to assess the contribution of the VOM in achieving MI conduction block. Methods This study included 143 consecutive patients with nonparoxysmal atrial fibrillation who underwent initial MI ablation. They were retrospectively classified into two groups, a VOM‐guided group (n = 28) and a conventional group (n = 115), according to the use of a 2‐Fr electrode cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…Ablation targeting the insertion sites achieved mitral line block in 75% patients. Similar findings were also demonstrated by Fujisawa et al 25 who demonstrated that one‐third of the patients showed a pseudo‐block during mitral isthmus ablation that was verified both in the VOM and CS electrodes.…”
Section: The Lom and Atrial Arrhythmiassupporting
confidence: 88%
See 1 more Smart Citation
“…Ablation targeting the insertion sites achieved mitral line block in 75% patients. Similar findings were also demonstrated by Fujisawa et al 25 who demonstrated that one‐third of the patients showed a pseudo‐block during mitral isthmus ablation that was verified both in the VOM and CS electrodes.…”
Section: The Lom and Atrial Arrhythmiassupporting
confidence: 88%
“…A recent study by Barrio‐Lopez et al 34 also reported a prevalence of 13.5% (72/534) for the presence of epicardial connections between PVs and other anatomic structures. As mentioned above, the LOM serves as not only an arrhythmogenic source of AF but also as a portion of re‐entry circuit for macro‐re‐entrant AT after AF ablation 20,22–26 . Epicardial ablation of LOM is a feasible and effective option, which does not appear to increase the complication risk.…”
Section: Targeting the Lom For Ablationmentioning
confidence: 99%
“…This may create a selective block towards the CS multipolar catheter but not to the entire MI. Presumably, some cardiac bundles may remain intact, and as we have learned, these may be located in the myocardial coverage of the vein of Marshall, the complex anatomical region of the LA ridge, the lateral aspect of the LAA base, or the area between the LAA and the mitral annulus [18][19][20][21]. Apparently, the impulse is passing through the remaining MI connections with a very long delay.…”
Section: Technical Aspects Of MI Ablationmentioning
confidence: 99%
“…This can lead to the persistence of conduction gaps that allow the maintenance of PMF despite the apparent evidence of complete block. This is a condition often referred to as MI pseudo-block [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…MI thickness and length may impact acute and long‐term success. The VOM bundle has more recently been identified as an important anatomical factor, and is protected from endocardial RF by adipose tissue insulation 14,15,57,58,71,72 . Several reports have shown its role in a substantial proportion of cases of MI reconnections, promoting additional RF in the CS lumen or left PV/LAA ridge during MI ablation (connecting areas of the VOM) 9,10,73 .…”
Section: Clinical Implications: the Importance Of MI Blockmentioning
confidence: 99%